Factors Associated with Blood Sugar Control Behavior on Patients with Diabetes Mellitus in Blang Kuta Community Health Center Area, Pidie Jaya District in 2023 - Mutiara; Tahara Dilla Santi; Wardiati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Diabetes mellitus has become one of the increasingly alarming global health challenges. As a chronic disease, diabetes results in various detrimental consequences, including high mortality rates and significant healthcare costs. Objective: This research aims to determine the factors associated with blood sugar control behavior among diabetes mellitus patients in the Blang Kuta Community Health Center's service area. Method: This study is a quantitative research with a cross-sectional approach. The population in this study consists of all DM patients in 4 villages in the Blang Kuta Community Health Center's service area, totaling 252 individuals. Sampling was conducted using proportional random sampling techniques, involving 72 DM patients. Data collection was performed through interviews using questionnaires and analyzed through univariate, bivariate analysis using chi-square test, and multivariate analysis using logistic regression test using the SPSS program. Result: The univariate analysis results revealed that the majority of respondents exhibited poor behavior (54.2%). Bivariate analysis results indicated a significant relationship between knowledge (p-value 0.000), level of education (p-value 0.002), gender (p-value 0.005), and self-efficacy (p-value 0.000) with blood sugar control behavior. However, variables such as family history (p-value 0.471) and duration of diabetes mellitus (p-value 0.277) did not show a significant relationship. Multivariate analysis results indicated that knowledge (p-value = 0.035, OR = 5.114) and self-efficacy (p-value = 0.000, OR = 13.278) are important determinants of blood sugar control among patients with diabetes mellitus. Conclusion: There is a significant relationship between knowledge, education, gender, and self-efficacy with blood sugar control behavior. However, variables such as family history of diabetes mellitus and duration of diabetes mellitus do not show a significant relationship. Nonetheless, factors strongly associated with blood sugar control behavior in diabetic patients are knowledge and self-efficacy.